Problematika Peralihan Kurikulum 2013 Menuju Kurikulum Merdeka Terhadap Kemampuan Numerik Peserta Didik - Karuna Dewi, Tri (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2022)
The curriculum is a guideline for carrying out learning activities to achieve educational goals, because the curriculum is the foundation of education. The purpose of this research is to identify the curriculum transition process that educators must adapt to, as well as barriers in the K-13 curriculum transition to independent learning. The method used is qualitative, this research uses documentation, interviews and observation techniques. The conclusion from the results of the analysis is as follows: the independent learning curriculum at SD Negeri 1 Pokoh Kidul has been implemented starting at the end of the 2022 academic year, by considering several factors, then preparing the tools, media and guidelines used in learning. The adaptation process for mathematics educators is carried out by applying the Pancasila student profile in learning and participating in a number of trainings to increase the capacity of educators. Barriers to this transition lie in human resources, teacher capacity and differences in students' awareness, thoughts and ways of thinking in understanding independent programs